Human Immunodeficiency Virus Type 1 Infection Is Associated with Increased NK Cell Polyfunctionality and Higher Levels of KIR3DL1+ NK Cells in Ugandans Carrying the HLA-B Bw4 Motif - Eller, Michael A.; Koehler, Rebecca N.; Kijak, Gustavo H.; Anne Eller, Leigh; Guwatudde, David; Marovich, Mary A.; Michael, Nelson L.; de Souza, Mark S.; Wabwire-Mangen, Fred; Robb, Merlin L.; Currier, Jeffrey R.; Sandberg, Johan K. (The Journal of infectious diseases, 2000)
Natural killer (NK) cells are important innate effector cells controlled by an array of activating and inhibitory receptors. Some alleles of the inhibitory killer-cell immunoglobulin-like receptor KIR3DL1 in combination with its HLA class I ligand Bw4 have been genetically associated with slower HIV-1 disease progression. Here, we observed that the presence of HLA-B Bw4 was associated with elevated frequencies of KIR3DL1 CD56dim NK cells in chronically HIV-1-infected individuals from the rural district of Kayunga, Uganda. In contrast, levels of KIR2DL1 CD56dim NK cells were decreased, and levels of KIR2DL3 CD56dim NK cells were unchanged in infected subjects carrying their respective HLA-C ligands. Furthermore, the size of the KIR3DL1 NK cell subset correlated directly with viral load, and this effect occurred only in HLA-B Bw4 patients, suggesting that these cells expand in response to viral replication but may have relatively poor antiviral capacity. In contrast, no association with viral load was present for KIR2DL1 and KIR2DL3 NK cells. Interestingly, chronic HIV-1 infection was associated with an increased polyfunctional response in the NK cell compartment, and, upon further investigation, KIR3DL1 CD56dim NK cells exhibited a significantly increased functional response in the patients carrying HLA-B Bw4. These results indicate that chronic HIV-1 infection is associated with increased NK cell polyfunctionality and elevated levels of KIR3DL1 NK cells in Ugandans carrying the HLA-B Bw4 motif.
Keywords: Human Immunodeficiency Virus Type 1 Infection; NK Cell Polyfunctionality; KIR3DL1+ NK Cells; Ugandans; HLA-B Bw4 Motif